A critical approach towards jade axes in southern Scandinavia - Sørensen, Lasse (Danish Journal of Archaeology, 2012)
Southern Scandinavian jade axes have been interpreted as items of prestigious exchange illustrating contact with the agrarian societies of Central Europe and reflecting agrarian ideas and ideology. They are therefore important in the discussion concerning the process of neolithisation in Northern Europe, but the difficulties in differentiating between Neolithic axes of alpine jade from axes imported from other continents has attracted some criticism. Furthermore, some of the jade axes found in Southern Scandinavian collections originate from private collectors, many of whom had contacts all over Europe. The axes lack therefore secure archaeological contexts, and may suggest that they have not been found in Scandinavian soil. The aim of this paper is to maintain a critical approach towards the question of the origin of the jade axes from Southern Scandinavia. However, the many imitations of jade axes produced in local raw materials clearly indicate the importance of this artefact group within the Mesolithic and Neolithic transition in Southern Scandinavia.